Implementation Acceptance Data Management Using Qr-Code - Amalia, Putri Sarah; Syahputra, Edy Rahman; Andriani, Septiana Dewi (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2021)
In the Medan johor sub-district, currently the filing management system is still manual, such as currently outgoing letters are still carried out in writing and if files are to be searched, they are still done manually by opening a ledger to see the file number or code so that document data is often inaccurate, The loss of documents then the problem of filing an ektp is still done manually for receipt of application for making an e-ktp so there is a need for a system that can record documents and perform computerized management of archives so that staff can easily manage the available archives. The author will implement a manual system that becomes computerized and a web-based system using Qr code technology with the aim that the archival processing system can be easily seen, managed, found and reused and minimizes loss of data required for future needs. This research is implemented by developing software, namely Extream Programming. System development is made faster and reduces costs from software changes. Keyword : Qr Code, Documents, Systems, Extream Programming